Reviving the dead land in Islamic jurisprudence Iraqi law (Journal of the College of Basic Education, 2022)
Reviving the dead land in Islamic jurisprudence and Iraqi law This research revolves around the reforms of the dead land, one of which has not advanced to the last to repair and revive it. And reviving the dead land is one of the important things that you write, these reasons are the reasons why it is very large, and also contribute greatly to increasing the economic resources that return to your economic nature that returns to investing in the economy, including economic education.